Brain death in children: is computed tomography angiography reliable as an ancillary test? - BIYIKLI, ERHAN; YAPICI, ÖZGE; ÖZTÜRK, MAKBULE NİLÜFER (My University, 2023)
Background The diagnosis of brain death is primarily clinical. Sometimes ancillary tests are needed.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Nükleer Tıp; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Nuclear medicine; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; Pediatri; Radyoloji, Nükleer Tıp ve Görüntüleme; Radyoloji ve Ultrason Teknolojisi; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Radiology, Nuclear Medicine and Imaging; Radiological and Ultrasound Technology; Pediatrics, Perinatology and Child Health; Ancillary test; Brain death; Cerebral vessels; Children; Computed tomography angiography; CT ANGIOGRAPHY; CONFIRMATORY TEST; DIAGNOSIS; PERFUSION; RELIABILITY